Emergency Management of Priapism in the United Kingdom: A Survey of Current Practice. Issue 4 (14th February 2018) - Bullock, Nicholas; Steggall, Martin; Brown, Gareth
Abstract: Background: Despite its importance, current practice in the emergency management of priapism in the United Kingdom is unknown. Aim: To evaluate current practice in the emergency management of priapism in the United Kingdom. Methods: All "full, " "associate urological specialist, " and "trainee" members of the British Association of Urological Surgeons (BAUS; leading membership-based organization for practitioners of urologic surgery in the United Kingdom) were invited to participate in an online survey. Questions related to the emergency management of priapism, access to tertiary andrology services, and use of guidelines. Outcomes: Key outcome measures included frequency of encountered cases, access to specialist andrology support, confidence in key management steps, and use of current guidelines. Results: 213 of 1, 304 (16.3%) eligible members completed the survey. Most reported managing 1 case annually (median = 1, range = 0–>10). Only 7.0% transferred patients to a tertiary center and 87.8% believed they could access specialist andrology advice if required. Respondents were less confident in performing intracavernosal phenylephrine instillation (88.7%) compared with corporal aspiration (98.1%), with confidence lowest among trainee members. Only 68.5% reported performing the distal shunt procedure. Of the 212 respondents that chose to answer questions relating to guidelines, only 155 (73.1%) were aware of their existence, with those published by the European Association of Urology being most popular (53.8%). 205 (96.2%) respondents expressed an interest in the development of a UK-specific guideline, with 162 of 212 (76.4%) stating they would use this in practice. Clinical Implications: Urologists in the United Kingdom support the development of UK-specific guidance on the emergency management of priapism for use within the context of the National Health Service. Strengths and Limitations: This is the first study to assess current practice in the emergency management of priapism in the United Kingdom. Its strength is that most UK urologists were invited to participate through collaboration with the BAUS. Although the response rate of 16.3% is acceptable for a national survey of this nature, responses were self-reported, rendering them susceptible to bias. Conclusion: This study demonstrates that some UK urologists lack confidence in key steps in the emergency management of priapism and identifies a strong level of support for the development of up-to-date UK-specific guidance.